BO‘LAJAK FIZIKA O‘QITUVCHISINING AXBOROT KOMMUNIKATIV KOMPETENTLIGINI AKT YORDAMIDA RIVOJLANTIRISH - Kadirimbetova, G.R. (SCIENCE and SOCIETY, 2022)
The article discusses the results of research to determine the level of formation of students' information-communicative competence. The experimental work carried out within the framework of the research work is aimed at forming the information-communicative competence of future physics teachers. The use of information technologies in the educational process helps to develop the creative and learning activity of students in their specialty.
Keywords: information and communication technologies; elektronik textbook; elektronik board; graphic program